Model-independent Estimators for the Statistical Anisotropy of the Cosmic Microwave Background - Shtanov, Yu.V.; Savchenko, D.O. (Ukrainian Journal of Physics, 2022)
We construct estimators for testing the statistical anisotropy of the cosmic microwave background arising due to a quadrupole scale-independent anisotropy in the primordial power spectrum. The estimators do not require the knowledge of basic cosmological parameters. We determine the sensitivity of the constructed estimators to the magnitude of the statistical anisotropy and perform test simulations that confirm our theoretical estimates.